Climate Change and Food Security: Steps towards Sustainable Development Goals - Fahmida; Chaudhary, Amatul Razzaq; Hanif, Uzma (iRASD Journal of Economics, 2022)
With the commendation of Sustainable Development Goals (SDGs) by the United Nations in 2015, the whole world is trying to accomplish these goals. All countries of the world are making efforts to achieve these goals. As compared to developed countries, developing countries are still far behind on the track of the sustainable development agenda. Realizing the goal of Zero Hunger (SDG 2) under climate change proves to be "challenging". Climate change can potentially be associated with eradicating hunger (SDG 2) worldwide, specifically in South Asia. Food security is considered a prerequisite to eradicating hunger and remains a challenge for developing countries. The study reconnoiters the potential footprints of climate change along with socio-economic variables on food security in climate-vulnerable food-insecure economies of Asia from 1980 to 2020. This study examines the impacts of variations in temperature on the supply of cereals for human consumption. The method of ARDL/PMG has been employed. There are two widely used techniques, i.e. FMOLS and DOLS, have also been employed to check the strength of the results. Outcomes of panel ARDL/PMG show that average yearly change in temperature has substantial and positive impacts on food security in the long run, but the square of the annual average change in temperature adversely and significantly impacts food security. Climate change has substantial and adverse effects on the food security of Bangladesh, Myanmar and Nepal but positive effects on Pakistan in the short run. From empirical outcomes, generalized and widespread policy guidelines have been endorsed to achieve food security (SDG 2) in the climate-vulnerable food-insecure economies of Asia. The study recommends evidence-based policy implications for the stakeholders of Asian economies.